Strong hydroclimatic controls on vulnerability to subsurface nitrate contamination across Europe - R. Kumar (Nature Portfolio, 2020)
Excess fertilizer use causes subsurface contamination. Here, the authors conduct an assessment of water quality vulnerability across Europe, finding that 75% of agricultural regions are susceptible to nitrate contamination for least one-third of the year, two times more than using standard estimation procedure.